A nonsense mutation in the tyrosinase gene of Afghan patients with tyrosinase negative (type IA) oculocutaneous albinism. - Giebel, L B (1991)
We detected a nonsense mutation in the tyrosinase gene of two Afghan sibs with classical tyrosinase negative (type IA) oculocutaneous albinism. The mutation, a single base substitution at codon 178, creates an amber termination codon that truncates the 529 amino acid tyrosinase polypeptide at this position. The patients' parents are first cousins, and the patients are therefore homoallelic for this mutation.